Comprehensive Study of Stereolithography and Digital Light Processing Printing of Zirconia Photosensitive Suspensions - Patrik Sokola; Petr Ptáček; Arijeta Bafti; Ivana Panžić; Vilko Mandić; Jan Blahut; Michal Kalina (Ceramics)
Zirconia ceramics are used in a wide range of applications, including dental restorations, bioimplants, and fuel cells, due to their accessibility, biocompatibility, chemical resistance, and favorable mechanical properties. Following the development of 3D printing technologies, it is possible to rapidly print zirconia-based objects with high precision using stereolithography (SLA) and digital light processing (DLP) techniques. The advantages of these techniques include the ability to print multiple objects simultaneously on the printing platform. To align with the quality standards, it is necessary to focus on optimizing processing factors such as the viscosity of the suspension and particle size, as well as the prevention of particle agglomeration and sedimentation during printing, comprising the choice of a suitable debinding and sintering mode. The presented review provides a detailed overview of the recent trends in preparing routes for zirconium oxide bodies; from preparing the suspension through printing and sintering to characterizing mechanical properties. Additionally, the review offers insight into applications of zirconium-based ceramics.